Nucleon Momentum Distributions and Elastic Electron Scattering FormFactors for some sd-shell Nuclei - Hamoudi, Adel; Flaiyh, Gaith; Mohsin, Sadeq (Iraqi Journal of Science, 2024)
The nucleon momentum distributions ( NMD) for the ground state and elasticelectron scattering form factors have been calculated in the framework of the coherentfluctuation model and expressed in terms of the weight function (fluctuation function).The weight function has been related to the nucleon density distributions of nuclei anddetermined from theory and experiment. The nucleon density distributions( NDD ) isderived from a simple method based on the use of the single particle wave functions ofthe harmonic oscillator potential and the occupation numbers of the states. The feature oflong-tail behavior at high momentum region of the NMD has been obtained using boththe theoretical and experimental weight functions. The observed electron scattering formfactors for Cl Cl 35 37 , and K 39 nuclei are very well reproduced by the presentcalculations throughout all values of momentum transfer q.PACS: 25 . 30 .Bf.